Bioenergetic Model Sensitivity to Diet Diversity Across Space, Time and Ontogeny - Lawson, Christopher L.; Taylor, Matthew D.; Smith, James A.; Payne, Nicholas L.; Semmens, Jayson M.; Suthers, Iain M.; Brodie, Stephanie (Frontiers in Marine Science, 2021)
Consumption is the primary trophic interaction in ecosystems and its accurate estimation is required for reliable ecosystem modelling. When estimating consumption, species’ diets are commonly assumed to be the average of those that occur among habitats, seasons, and life stages which introduces uncertainty and error into consumption rate estimates. We present a case study of a teleost (Yellowfin Bream Acanthopagrus australis) that quantifies the potential error in consumption (in mass) and growth rate estimates when using diet data from different regions and times and ignoring ontogenetic variability. Ontogenetic diet trends were examined through gut content analysis (n=1130 fish) and incorporated into a bioenergetic model (the ‘primary’ model) that included diet variability (n=144 prey sources) and ontogenetic changes in metabolism (1 – 7 y) to estimate lifetime consumption. We quantified error by building nine model scenarios that each incorporated different spatiotemporal diet data of four published studies. The model scenarios produced individual lifetime consumption estimates that were between 25% lower and 15% higher than the primary model (maximum difference was 53%, range 11.7 kg to 17.8 kg). When consumption (in mass) was held constant, differences in diet quality among models caused a several-fold range in growth rate (0.04 – 1.07 g d-1). Our findings showcase the large uncertainty in consumption rate estimates due to diet diversity, and illustrate that caution is required when considering bioenergetic results among locations, times and ontogeny.